ENT300 Fundamental of Entrepreneurship Business Model Canvas (Hannahonne Enterprise) / Nurul Hanna Che Rusli - Che Rusli, Nurul Hanna (2020)
HANNAHONNE ENTERPRIS is a print shop that prints and copies things such as documents and cards. We also do a handheld device for inking and imprinting a message or design on a surface which called rubber stamp for customers that will give maximum satisfaction and brings excitement for them. This company is owned by Nurul Hanna Binti Che Rusli. This is family business that started from her father. A printing business is one of the best business to start with. This is because, the market is wide and growing so that the business opportunity is very high. There is a lot types of printing such as banner, poster, business card and so on. Look people around us, they are wearing shirt can be an opportunity for you to sell printed t-shirt. Company with more than 50 workers might use ID card printed with their employee picture and employee details. Other than that, you can also print business cards, invitation cards, calendar, hang tag or label, letterhead, bags, stickers, posters, mugs, brochures and others.